Healthcare resource utilization patterns in psoriasis patients using biologic and conventional treatments in Finland - Vesikansa, Aino; Mehtälä, Juha; Aaltonen, Jaakko; Konttinen, Riikka; Tasanen, Kaisa; Huilaja, Laura (Frontiers in Immunology, 2024)
Introduction and aim Psoriasis vulgaris is associated with a significant healthcare burden, which increases over time as the disease progresses. The aim of this retrospective, population-based registry study was to characterize healthcare resource utilization (HCRU) in patients with psoriasis using biologics and oral immunosuppressants (conventionals) in Finland. Materials and methods The study cohort included all patients with a diagnosis of psoriasis vulgaris in the secondary healthcare setting between 2012–2018, who initiated a biologic (n=1,297) or conventional (n=4,753) treatment between 2013–2017. Data on primary and secondary HCRU were collected from nationwide healthcare registries. Results The results indicated a remarkable decrease in contacts with a dermatologist after the treatment initiation among patients starting biologic (mean annual number of contacts 5.4 per person before and 2.3 after the initiation), but not conventional (3.3 and 3.2) treatment. For conventional starters there was a high level of contacts with a dermatologist surrounding times of treatment switching, which was not observed for biologic starters. Conclusion Overall, primary and other secondary care contacts did not decrease after the initiation or switch of treatment. The results highlight the importance of thorough consideration of the most optimal treatment alternatives, considering the overall disease burden to patients and healthcare systems.